Legacy effects of an atmospheric heatwave are buffered by mutualistic interactions between intertidal clams and seagrass - Román, Marta; Vázquez, Elsa; Weidberg, Nicolás; Viejo, Rosa M.; Román, Salvador; Troncoso, Jesús S.; Wethey, David S.; Woodin, Sarah A.; Olabarria, Celia (Frontiers in Marine Science, 2025)
More intense and frequent atmospheric heatwaves in the future may reduce the growth and survival of intertidal organisms. However, interspecific facilitative interactions can buffer legacy effects of thermal stress and favor recovery of the affected organisms. To test the role of facilitation, we exposed assemblages of Zostera noltei and juveniles of Venerupis corrugata, Ruditapes decussatus and R. philippinarum to a low-tide atmospheric heatwave in mesocosm experiments. A four-hour low-tide emersion period was applied daily for four consecutive days. During the heatwave, the temperatures of 108 experimental units were monitored withhermocouples. Assemblages were transplanted to two intertidal flats (Combarro and Noia) in NW Spain, and different temperature, salinity and nutrient concentrations were measured during the experiment. After two and a half months, there were no differences in shoot abundance or above-ground biomass between seagrass affected by legacy heat stress and control seagrass growing together with clams; however, the values of both variables were lower in the seagrass only scenario, suggesting clam-derived facilitation. At Combarro, characterized by higher temperature and salinity, a mutualistic interaction between clams and Z. noltei was observed, with greater above-ground biomass and more abundant shoots in the seagrass and enhanced growth of clams. No such interactions were observed at Noia, where the seagrass biomass was significantly lower than at Combarro. At Noia, characterized by higher nutrient concentrations in seawater, the presence of Ulva spp. canopies above the seagrass and higher levels of N in Z. noltei shoots indicated that eutrophic conditions hampered seagrass growth and mutualistic interactions with clams. The findings suggest that species-specific responses and abiotic context shape the magnitude and direction of ecological interactions.